Outcomes After Central Wedge Labiaplasty Performed Under General Versus Local Anesthesia. Issue 1 (July 2021) - Nwaoz, Basil; Sinnott, Catherine J.; Kuruvilla, Annet; Natoli, Noel B.
Abstract : Purpose: Interest in labiaplasty as a way to alter and improve genital appearance has been on the rise. Labiaplasty procedures can be performed in the office setting under local anesthesia. However, these procedures are often performed under general anesthesia for patient comfort and to facilitate the operative technique and to potentially improve outcomes. Outcomes after labiaplasty performed under general anesthesia as compared with that performed under local anesthesia in the office setting have not been well-defined. This article aimed to compare outcomes after central wedge labiaplasty performed under general anesthesia versus that performed under local anesthesia. Methods: A retrospective chart review identified patients who underwent central wedge labiaplasty performed by a single surgeon from 2011 to 2019. Demographic, clinical, and operative information were reviewed and recorded. Outcomes were assessed by evaluating postoperative complications and the need for revision surgery. Results: Thirty-two women with a mean age of 32.8 ± 11.2 years and a mean body mass index of 22.0 ± 3.5 kg/m 2 underwent central wedge or extended central wedge labiaplasty during the study period. Ten (31.2%) labiaplasties were performed under local anesthesia in an office setting, and 22 (68.8%) were performed under general anesthesia. Demographic, clinical, and operative characteristics were comparable between labiaplasties performed under local anesthesia and those performed under general anesthesia. Postoperative asymmetry and wound dehiscence were the most common complications. Outcomes after labiaplasty performed under general anesthesia were comparable to those performed under local anesthesia, with regard to asymmetry (27.3% vs 10.0%; P = 0.387), dehiscence (27.3% vs 40.0%; P = 0.683), scarring (4.5% vs 0.0%; P = 1.000), and the need for revision surgery (31.8% vs 40.0%; P = 0.703), respectively. There were no cases of infection, hematoma, decreased sensation, or dyspareunia. Conclusions: Postoperative asymmetry and dehiscence were the most common complications after labiaplasty performed under general or local anesthesia. Outcomes after labiaplasty performed under general anesthesia were comparable to those performed under local anesthesia. Further studies are needed to assess outcomes after labiaplasty performed under general anesthesia versus that performed under local anesthesia.